Impact of Infrastructure Development on Property Prices in Developing Urban Areas: A Systematic Review - Artiani, Gita; Oei Fuk Jin (Rekayasa Sipil, 2026)
Research on the relationship between infrastructure development and property values remains essential in the context of rapid urbanization. While existing studies predominantly highlight direct influences such as transportation networks and public amenities, limited attention has been given to broader dimensions, particularly sustainability and smart technologies. This study contributes to the literature by systematically reviewing publications from 2020 to 2025, highlighting how infrastructure development influences property prices through sustainable urban planning and the integration of smart infrastructure. Using the Systematic Literature Review (SLR) method supported by bibliometric tools (VOSviewer and Publish or Perish), this research identifies four major themes: accessibility, public service provision, regulatory frameworks, and the adoption of green and smart technologies. The findings reveal that although the positive correlation between infrastructure and property values is well established, gaps remain in addressing long-term impacts of green building strategies, energy efficiency, and the economic implications of smart infrastructure. The novelty of this study lies in framing these underexplored themes as emerging research priorities, offering new insights for policymakers, urban planners, and developers in aligning infrastructure investment with sustainable and technologically adaptive urban growth.